Cyclo (Tyrosyl-Prolyl) Produced by Streptomyces sp.: Bioactivity and Molecular Structure Elucidation - ROFIQ SUNARYANTO; BAMBANG MARWOTO; LIESBETINI HARTOTO; ZAINAL ALIM MAS'UD; TUN TEDJA IRAWADI (Microbiology Indonesia, 2011)
Determination of bioactivity by minimum inhibitory concentration (MIC) methods and molecular structure identification of antibiotic produced by Streptomyces sp. have been carried out. The antibiotic was produced by liquid culture using Streptomyces sp. isolate. Purification of antibiotic was carried out by silica gel column chromatography and preparative HPLC. Molecular structure identification was carried out using ESI-MS, 1H NMR, 13C NMR, and 13C DEPT NMR. Pure antibiotic showed inhibition activity to Gram-negative and Gram-positive bacteria. MIC to Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC27853 , Staphylococcus aureus ATCC25923, and Bacillus subtilis ATCC66923 were 27.0, 68.7, 80.2, and 73.7 μg mL-1 , respectively. Identification using ESI-MS showed that the molecular weight of this antibiotic was 260 g mol-1 , and molecular formula was C14H16N2O3 . Elucidation of molecular structure using 1HNMR, 13C NMR, and 13C DEPT NMRshowed that antibiotic was cyclo(tyrosyl-prolyl).